Comparison of Parent, Peer, Psychiatric, and Cannabis Use Influences Across Stages of Offspring Alcohol Involvement: Evidence from the COGA Prospective Study. (10th January 2017) - Bucholz, Kathleen K.; McCutcheon, Vivia V.; Agrawal, Arpana; Dick, Danielle M.; Hesselbrock, Victor M.; Kramer, John R.; Kuperman, Samuel; Nurnberger, John I.; Salvatore, Jessica E.; Schuckit, Marc A.; Bierut, Laura J.; Foroud, Tatiana M.; et al.
Abstract : Background: All stages of development of alcohol use disorder (AUD) have not been equally studied. While initiation of drinking has been given considerable attention, other stages have not been as thoroughly investigated. It is not clear whether the same factors are associated consistently across early and late transitions in AUD involvement. High‐risk family samples that are enriched for AUD vulnerability and transitions in AUD development offer an opportunity to examine influences across multiple stages of AUD development. Methods: Data from adolescents and young adults from high‐risk families were used to study 4 transitions in AUD development—time to first drink, first drink to first problem, first drink to first diagnosis, and first problem to first diagnosis. Cox modeling was used to compare associations of parental AUD, parental separation, peer substance use, offspring ever‐use of cannabis, trauma exposures, and internalizing and externalizing psychopathology across transitions. Results: Hazards of most transitions were elevated for those who had ever used cannabis, those who attributed substance use to their peers, those with externalizing disorders, and those with parents with AUD. Many risk factors were linked to early initiation of alcohol, particularly cannabis use. Internalizing disorders were associated with later stages. Nonassaultive trauma was associated only with early initiation; assaultive trauma was not associated with any transition. Conclusions: In this large, ethnically diverse sample of high‐risk youth, significant influences across transitions were fairly consistent, with externalizing disorders and cannabis ever‐use elevating the likelihood of each stage, and peer and parental (and especially maternal AUD) influences linked to initiation and some later stages. Finally, in light of the increasingly permissive legal and social stances toward cannabis in the United States, the marked elevations of all alcohol outcomes observed for cannabis use underscore the importance of studying the underpinnings of this relationship. Abstract : Development of alcohol use disorder was decomposed into 4 stages: time to first drink, from first drink to first problem and from first drink to first AUD diagnosis, and from first problem to first diagnosis, in high‐risk youth. Significant influences were consistent, with cannabis ever‐use and externalizing disorders elevating the likelihood of each stage, and peer and parental AUD linked to 3 of 4 stages. The marked elevations of all AUD stages for cannabis use underscore the importance of studying this relationship.